Patient engagement in action: Timing and intensity of strategies used to engage low income depressed mothers of infants and toddlers - Maureen Baker (The Beryl Institute, 2020)
The purpose of this study was to illuminate the process of patient engagement and to determine how components of patient engagement were operationalized in the nurse-patient interpersonal relationship with low income, depressed mothers, a traditionally underserved population. Using a descriptive quantitative design, we examined how components of patient engagement were executed across three phases of the nurse-patient interpersonal relationship. We assessed for differences in engagement strategies used in different phases of the interpersonal relationship and with mothers with varying levels of engagement. Through this study, we observed that patient engagement has several dynamic components varying in intensity and frequency, depending on the phase of the nurse-patient relationship. Mothers varied in their degree of engagement. Lack of engagement by mothers limited the nurses’ use of engagement skills and strategies, thus underscoring the importance of effort and time spent in the orientation phase. Findings from this study can inform and advance the science of patient engagement by expanding the knowledge base and understanding as to the rhythm and flow of patient engagement in practice. Patient engagement requires persistence and variation of engagement strategies to establish an ongoing interpersonal relationship with patients. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.